Exchange Rate Regimes and Market Interactions between Onshore and Offshore Markets for Chinese Yuan - Tutti, Henriikka (My University, 2012)
The purpose of this thesis is to investigate the interrelation and information flows in returns and volatilities between the dollar-yuan spot, onshore forward and offshore forward (NDF) markets. The study focuses on the impact of changes in the yuan exchange rate regimes, which occurred in August 2008 and July 2010. Moreover, the study tests the unbiased forward rate hypothesis and examines which one of the exchange rates is the best predictor of the future level of the spot rate. The data consists of daily closing rates of the USD/CNY spot, 1-month deliverable forward and 1-month NDF rates. The sample period starts from October 20, 2005 and ends in August 31, 2011. The sample period is divided into three separate sub-sample periods to represent different exchange rate systems in place. The main results are following. The unbiased forward rate hypothesis does not hold. The best but not unbiased predictor of the future spot rate is the NDF rate. There exist two-way causal relationships between all three markets during the dollar-peg and less causal relationships during the managed float periods. Significant mean spillover effects across markets are found in every sample period. Strong and statistically significant persistence of volatility and co-volatility between the markets is found in every sample period. Moreover, there is a weak but statistically significant impact of shocks between market volatilities and on markets own volatility. The results suggest that these markets share common fundamentals and that news about the fundamentals in one market is useful to investors in the other markets. Thus, the markets fail to process news efficiently and are indeed interrelated with each other. Changes in exchange rate regimes have affected these relations.
Keywords: renminbi; yuan; non-deliverable forward (NDF); foreign exchange market; market efficiency; unbiased forward rate hypothesis; spillover effect; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|